Efficacy of Biofungicide with Active Ingredients Trichoderma sp. Against Late Blight Disease (Phytophthora infestans) in Potato Plants - Abadi, Abdul Latief; Trianti, Irisa; Choliq, Fery Abdul; Sektiono, Antok Wahyu; Yulianti, Novi Dwi (Universitas Panji Sakti, 2024)
The cultivation of potatoes in Indonesia faces challenges, particularly a decline in production attributed to the devastating impact of late blight caused by the fungus P. infestans. Traditional control methods involve the frequent use of chemical pesticides, which pose environmental and health risks. To address this, the research aimed to assess the efficacy of biofungicide containing Trichoderma sp. as a biological agent in controlling late blight on potatoes. The study, conducted in Sumberbrantas Village, Bumiaji District, Batu City, East Java, and the plant disease laboratory at Brawijaya University from January to April 2023, employed both in vivo and in vitro experiments. A Randomized Block Design (RBD) was used for in vivo research, while a Completely Randomized Design (CRD) was employed for in vitro studies, each comprising five concentration treatments with five repetitions. Parameters such as disease intensity, efficacy level, potato production, and biofungicide inhibition were observed. Analysis of variance and the Tukey Honestly Significant Difference (HSD) test were applied to the data and processed using Microsoft Excel. The results indicated that biofungicide with Trichoderma sp. concentrations of 6 ml/l, 4.5 ml/l, 3 ml/l, and 1.5 ml/l effectively reduced the intensity of late blight on potatoes, with efficacy levels exceeding 50%. The highest potato production occurred with a concentration of 6 ml/l, yielding 15.44 tons/ha, followed by 14.67 tons/ha for the 4.5 ml/l concentration. The biofungicide with a concentration of 6 ml/l exhibited the lowest disease intensity at 14.28% and the highest efficacy at 83.08%. Inhibition tests demonstrated that concentrations of 6 ml/l and 4.5 ml were highly effective, inhibiting P. infestans growth by an average of 62.04% and 59.90%, respectively. These findings highlight the potential of biofungicide with Trichoderma sp. in managing late blight on potatoes, providing a sustainable and environmentally friendly alternative to chemical pesticides.